A multispecies companion: Architectural fictions of co-existence - Wahlstedt, Klara (My University, 2021)
We are building, renovating, gardening, cleaning up the environments that we call cities. We are organizing the world around ourselves, as humans, and we have the power to decide who’s wanted and unwanted inhabitants of those places. This thesis aims to open up discussions about what it would mean if we started to consider ourselves as multispecies citizens instead, and which encounters that could be used to emphasise this feeling. By starting to look for the presence of non-human species in the city with, I want to weave myself closer into the multispecies entanglements those places are created of. Letting them guide me towards new understandings about what architecture can be if we are leaving space for non-human agencies to get engaged. Guided by theorists, designers and architects working with questions concerning multispecies studies and posthuman perspectives, this thesis will step into the unknown terrain the city can become if we allow it. By exploring storytelling as a method for architectural understanding it wants to unfold new relations between us humans and the species that surround us, raising questions of co-existence and who to care for. This will be done by mapping and cataloguing already existing relations, and possible encounters, between humans and non-humans in the city of Gothenburg. These stories have then been expanded into fictions of imaginable futures. Fictions that aim to find other ways of relating to the multispecies lives that’s going on around us. The findings and knowledge revealed through this process will be communicated through a set of artefacts. Artefacts that aim to act as invitations to discussions and reveal new ways of looking at the city that surrounds us.
Keywords: Multispecies encounters, storytelling, urban environments, care, natureculture, agency, posthumanism